Tradução do conhecimento em amamentação : protocolo para prática clínica no alojamento conjunto - Salgueiro, Michele Anne de Oliveira Batista (2024)
Introduction: Breastfeeding is a complex, dynamic, and interactive process that depends on several factors that can influence it positively or negatively. This project aims to meet an institutional demand for improvements in breastfeeding care for newborns in rooming-in facilities, and is aligned with the research line on the organization and evaluation of health care systems. Objectives: To describe the knowledge and care practices of health professionals on breastfeeding. To develop a multidisciplinary protocol on breastfeeding. To implement the multidisciplinary care protocol on breastfeeding in the maternity ward. To evaluate changes in compliance with recommendations for evidence-based practices after the implementation of the protocol. Methodology: Participatory research, which used the Knowledge to Action Cycle model to implement a Knowledge Translation project. The study was carried out in a university hospital in Espírito Santo, Brazil, with the participation of the interprofessional team of the rooming-in facility and milk bank. In the knowledge cycle, the existing knowledge was assessed using the self-assessment questionnaire of the Baby-Friendly Hospital Initiative (BFHI); To develop the knowledge tool, a working group was formed with the interprofessional team, and the clinical protocol was developed based on the synthesis of knowledge. In the action cycle, theoretical and practical training was carried out; the protocol was implemented; the barriers and facilitators of the implementation process were assessed; and the impact was assessed through 3 strategies: 1) assessment of care indicators; 2) assessment of the knowledge and skills of health professionals; and 3) self-assessment as recommended in the IHAC self-assessment questionnaire; maintenance of the use of knowledge will be done through continuing education actions and events in Golden August. To analyze the qualitative data, the recordings of the groups were transcribed using an online tool, read exhaustively, and submitted to categorical content analysis. Results: Products: Protocol for breastfeeding premature and low-weight newborns. Flowcharts, process maps, and infographics to guide the work of employees and the role of parents in this process. Multidisciplinary and intersectoral training. Final considerations: This project achieved the objective of improving the evidence-based practice of the multidisciplinary team and enabled the development and implementation of the first protocol for breastfeeding care for newborns cared for in the institution's shared accommodation. The protocol and products have already been implemented and are generating positive impacts in the institution. This research has the potential to be applied at regional and national levels, as it systematically describes an innovative method with the steps and resources necessary for the implementation of the best scientific evidence. The research influenced changes in practice, but maintaining evidence-based care recommended in the protocol requires ongoing education of the neonatal team and other sectors involved to assist in adherence and better results